2013
DOI: 10.5194/cp-9-1029-2013
|View full text |Cite
|
Sign up to set email alerts
|

Spatial gradients of temperature, accumulation and δ<sup>18</sup>O-ice in Greenland over a series of Dansgaard–Oeschger events

Abstract: Abstract. Air and water stable isotope measurements from four Greenland deep ice cores (GRIP, GISP2, NGRIP and NEEM) are investigated over a series of Dansgaard–Oeschger events (DO 8, 9 and 10), which are representative of glacial millennial scale variability. Combined with firn modeling, air isotope data allow us to quantify abrupt temperature increases for each drill site (1σ = 0.6 °C for NEEM, GRIP and GISP2, 1.5 °C for NGRIP). Our data show that the magnitude of stadial–interstadial temperature increase is… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
89
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 83 publications
(109 citation statements)
references
References 113 publications
(191 reference statements)
17
89
3
Order By: Relevance
“…This sensitivity of δ 15 N has even been used to adjust temperature and/or accumulation rate scenarios (Buizert et al, 2013;Guillevic et al, 2013;Kindler et al, 2014;Landais et al, 2006). We tested the influence of the accumulation rate and temperature scenarios on the simulated δ 15 N profiles for the last deglaciation, but even with large uncertainties in the input scenarios, it is not possible to reproduce the measured Antarctic δ 15 N increase at Dome C and EDML with the old version of the LGGE model.…”
Section: Transient Run With the Old Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…This sensitivity of δ 15 N has even been used to adjust temperature and/or accumulation rate scenarios (Buizert et al, 2013;Guillevic et al, 2013;Kindler et al, 2014;Landais et al, 2006). We tested the influence of the accumulation rate and temperature scenarios on the simulated δ 15 N profiles for the last deglaciation, but even with large uncertainties in the input scenarios, it is not possible to reproduce the measured Antarctic δ 15 N increase at Dome C and EDML with the old version of the LGGE model.…”
Section: Transient Run With the Old Modelmentioning
confidence: 99%
“…The uncertainty in the temperature reconstructions can be estimated to ±3 • C over the last deglaciation in Greenland . As for the Greenland accumulation rate, an uncertainty of 20 % can be associated with the Last Glacial Maximum (LGM) value (Cuffey and Clow, 1997;Guillevic et al, 2013;Kapsner et al, 1995). In Antarctica, both temperature and accumulation rate are deduced from water isotopic records except for WAIS Divide, where layer counting back to the last glacial period is possible .…”
Section: Input Scenariosmentioning
confidence: 99%
See 1 more Smart Citation
“…This isotope-temperature relationship (isotope thermometer) (Johnsen et al, 2001) has been central to the use of ice core water isotope records to reconstruct past Greenland climate variations. However, the comparison of water stable isotope measurements with past temperatures inferred either from the inversion of borehole temperature data (DahlJensen et al, 1998) or from the fingerprint of firn air fractionation in ice core air δ 15 N has revealed that (i) for a given site, the isotope-temperature relationship varies through time (e.g., Guillevic et al, 2013;Landais et al, 2004;Kindler et al, 2013;Severinghaus and Brook, 1999), and (ii) for a given stadial-interstadial event, the isotope-temperature relationship varies between sites . The reported temporal isotope-temperature relationships vary between 0.3 and 0.6 ‰ • C −1 .…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, uncertainties also arise from the age scales of proxy records, and from the application of transfer functions used to convert proxy records into climate variables. For instance, while δ 18 O is used as a temperature proxy in polar ice cores, the relationship between ice core δ 18 O and temperature is known to vary through time and between drilling sites (Masson-Delmotte et al, 2011a;Guillevic et al, 2013;Buizert et al, 2014). Similarly, the relationship between δ 18 O from tree-ring cellulose and climate may be impacted by several factors, including local monthly or annual temperature and precipitation, while the response of trees to climate changes may differ according to inherent physiological differences of the various tree species (Stuiver and Braziunas, 1987;McCarroll and Loader, 2004).…”
Section: Introductionmentioning
confidence: 99%